Status report of the Heidelberg Radiocarbon Laboratory: precision and application in Mauritanian cold-water corals over the last 30,000 years - Beisel, Elvira; Therre, S.; Wienberg, C.; Friedrich, R.; Frank, Norbert (Radiocarbon, 2025)
Highly precise and reproducible radiocarbon (14C) measurements are regularly performed at the Heidelberg Institute for Environmental Physics, Heidelberg, Germany, in collaboration with the radiocarbon laboratory of the Curt-Engelhorn-Center Archaeometry in Mannheim, Germany. Here, we report an update of the technical details, focusing on the analysis of cold-water corals (CWC), and present an improved long-term blank value with a mean of (0.190 ± 0.064) pMC (n = 138) and excellent reproducibility of the IAEA-C2 standard with a mean of (41.15 ± 0.16) pMC (n = 75), consistent with its certified consensus value. Furthermore, 33 duplicates of the CWC 14C measurements agree within 2σ, 85% even within the 1σ range. This provides excellent conditions for accurate 14C measurements. As an application example, we present combined 230Th/U and 14C ages of a coral-bearing sediment core from the upper Mauritanian slope. The resulting ventilation age record confirms decreasing ventilation between 30 and 25 kyr BP, most likely reflecting a northward propagation of a water mass originating from the south. During the LGM, we confirm a previously hypothesized southward displacement of the Cap Verde Frontal Zone. With the onset of the deglaciation, our record documents again an advance of a southern-sourced water mass into the subtropical North Atlantic. During the Bølling-Allerød warm period, strong ventilation fluctuations possibly indicate temporal influence of southern-sourced water.
Online veröffentlicht: 14. März 2025
Gesehen am 11.08.2025